ANTIBODY RESPONSE OF BROILERS TO OIL BASED COMBINED AVIAN INFLUENZA (H9 N2) AND MYCOPLASMA GALLISEPTICUM VACCINE - S. Sarfaraz; K. Muhammad; T. Yaqub; A. Aslam; M. Rabbani; M. Khalil; R. Riaz (Journal of Animal and Plant Sciences, 2017)
Mycoplasmosis caused by Mycoplasma  gallisepticum (MG) and Avian influenza virus (AIV: H9N2) infection are serious health hazards for poultry. The AIV is low pathogenic but is cause of high morbidity and mortality in immunocompromised birds. On 7th day of age, each bird of group A, B and C (n=10) was vaccinated (0.3ml: I/M) with oil based O-MG, O-AIV and O-MG+AIV vaccine, respectively. Serum samples collected on 28, 35 and 42 days of age were processed for determination of anti-MG-ELISA antibodies and anti-AIV-HI antibodies. Antibody response of the birds to either immunogen of monovalent vaccines (O-MG and O-IV) was not significantly different (P>0.05) from antibody titers against both the immunogens in combined vaccine (O-MG+AIV). It is concluded that oil based combined O-MG+AIV vaccine induces effective antibody response in the vaccinated birds.
Keywords: Mycoplasma gallisepticum; Avian influenza (H9N2); immunogen; vaccine